Variety of symptoms of GLUT1 deficiency syndrome in three-generation family - Winczewska-Wiktor, Anna; Hoffman-Zacharska, Dorota; Starczewska, Monika; Kaczmarek, Izabela; Badura-Stronka, Magdalena; Steinborn, Barbara (Epilepsy & behavior, 2020)
Glucose transporter type 1 deficiency (G1D) syndrome is generally a genetic disorder because of a mutation of the SLC2A1 gene. The clinical picture of G1D is heterogeneous. The aim of this paper was to present the case of G1D, recognized in a three-generation family, caused by missense mutation p.Arg92Trp in SLC2A1 gene, and showing high clinical heterogeneity and evolution of symptoms over time. Three-generation family members, showing symptoms suggesting G1D, have been characterized in terms of the clinical picture, electroencephalogram (EEG) recordings, brain neuroimaging, and the psychological assessment data. All subjects were offered genetic testing of the SLC2A1 gene. We sequenced the SLC2A1 gene in the proband of the family and identified the c.274C > T variant (p.Arg92Trp). The presence of the same mutation was confirmed in all affected family members; however, significant variations in the clinical picture among them were observed. In addition to the typical symptoms for G1D (e.g., epilepsy, intellectual disability), patients presented movement disorders, stiffness, and dysarthria, as well as psychiatric symptoms. After using the ketogenic diet, epileptic seizures disappeared, but the rest of the symptoms were resistant to treatment. Despite the same underlying mutation, clinical symptoms may vary among members of one family. Different clinical symptoms are observed depending on the patient's age. Not all symptoms occur in all patients within one family despite the same genetic background. However, the importance of early therapy for the clinical course of the disease requires further study. •Glucose transporter type 1 deficiency (G1D) has high clinical variability.•It seems that there is rather a continuum of phenotypes than separate classification groups in G1D.•Early-onset drug-resistant epilepsy, developmental delay, and movement disorders are G1D symptoms.•A ketogenic diet is an effective treatment of epilepsy caused by a mutation in the SLC2A1 gene.•Within family, despite the same genetic background, different clinical manifestations may occur.